Sathiti thī kep rūaprūam dōi nūai sathiti kh̨ōng Prathēt Thai, pī ngoppramān 2537-2538 : chaph̨o nūai sathiti thī song khrōngkān mā yang Samnakngān Sathiti h̄æng Chāt (Samnakngān Sathiti h̄æng Chāt, Samnak Nāyok Ratthamontrī, 1996)
Statistical report of Thai government ministries, departments, and public enterprises, 1994-1995.